2009
DOI: 10.1002/ange.200902237
|View full text |Cite
|
Sign up to set email alerts
|

On the Role of Metal Contaminants in Catalyses with FeCl3

Abstract: Metal catalysis has a dominant role in modern organic chemistry. In particular, crosscoupling reactions allow bond formations, which have previously been impossible to perform. [1] Precious metal catalysts dominate the field, but alternative systems based on nickel and copper salts have also, historically, been important. In particular, recent systems based on these metals have been described that provide products in a highly efficient manner. [2] In this context, one of us (C.B.) reported iron-catalyzed cross… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
64
0
2

Year Published

2009
2009
2013
2013

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(67 citation statements)
references
References 47 publications
1
64
0
2
Order By: Relevance
“…For example, only 5 ppm of Cu 2 O catalyst could effectively catalyze the N-arylation reaction of pyrrazole or phenylamide, affording the corresponding product in good yield (77% and 97%, respectively). [6] Larsson et al [7] also found a similar effect and reported on Ullmann-type coupling reactions in the presence of "homeopathic amounts" of copper salts. Moreover, the scope of Ullmann-type reactions could be extended to N-, O-, and S-arylations with submol% amounts of copper.…”
Section: Introductionmentioning
confidence: 76%
“…For example, only 5 ppm of Cu 2 O catalyst could effectively catalyze the N-arylation reaction of pyrrazole or phenylamide, affording the corresponding product in good yield (77% and 97%, respectively). [6] Larsson et al [7] also found a similar effect and reported on Ullmann-type coupling reactions in the presence of "homeopathic amounts" of copper salts. Moreover, the scope of Ullmann-type reactions could be extended to N-, O-, and S-arylations with submol% amounts of copper.…”
Section: Introductionmentioning
confidence: 76%
“…Reducing the catalyst loading to 10 mol % ( Table 1, entry 5) resulted in a significant decrease in the yield of product. The use of FeA C H T U N G T R E N N U N G (acac) 3 of lower purity (> 94 %) gave a slightly lower yield (67 %), and the reactions with Cu 2 O or PdA C H T U N G T R E N N U N G (OAc) 2 , which are usual contaminant suspects in iron catalysis, [14] did not proceed at all under these conditions. The presence of a bipyridyl-type ligand to stabilize the catalytic iron species was essential (Table 1, entry 6), and dtbpy performed slightly better than 2,2'-bipyridine (bpy) or 1,10-phenanthroline (phen, Table 1, entries 7 and 8, respectively).…”
mentioning
confidence: 90%
“…[16] It is known that impurities present in commercially available metal salts can catalyze various reactions. [17] Taking into consideration that trace amounts of transition metals, which are known to catalyze direct arylation, can be present in t-BuOLi, some additional experiments were done to examine this issue. No difference in yield was noted in experiments when t-BuOLi from different sources was used.…”
mentioning
confidence: 99%